The Search for the Optimal cut-off Value of p53-Immunohistochemistry to Predict Prognosis of Invasive Bladder Cancer: A Multi-Center, Multi-Laboratory Analysis - Mertens, Laura S; Claps, Francesco; Mayr, Roman; Hodgson, Anjelica; Shariat, Shahrokh F; Hippe, Katrin; Neuzillet, Yann; Sanders, Joyce; Burger, Maximilian; Pouessel, Damien; Otto, Wolfgang; van der Kwast, Theo H; et al. (International journal of surgical pathology, 2023)
Introduction: Mutations in the TP53 gene are indicative of worse outcome in bladder cancer and are usually assessed by immunohistochemistry. To define p53-overexpression, a threshold of >10% is most commonly used (cut-off1). Recently, a novel cut-off (aberrant = 0% or ≥50%) (cut-off2) showed better correlation to clinical outcome. In this study, we evaluate the association between p53-immunohistochemistry cut-offs, clinico-pathological variables and disease-specific survival (DSS). Methods: Seven-hundred-fifty chemotherapy-naïve patients who underwent radical cystectomy were included (92% muscle-invasive bladder cancer. In addition to cut-off1 and cut-off2, a third cut-off (cut-off3) was determined based on the highest Youden-index value. Cut-off values were associated with clinico-pathological variables and FGFR3 mutation status. The Kaplan-Meier method was used to estimate DSS. Results: Aberrant p53-expression was found in 489 (65%) (cut-off1) and 466 (62%) (cut-off2) tumors. Cut-off3 was determined at 25% and aberrant p53-expression in 410 cases (55%) (cutoff3). p53-expression levels were significantly associated with higher pT-stage (cut-off1/2/3: P = 0.047, P = 0.006 and P = 0.0002, respectively), higher grade (all, P < 0.0001), and FGFR3 wild-type (cut-off1: P = 0.02, cut-offs2&3: P = 0.001). Median follow-up was 5.3 years (interquartile range, 4.0-6.0 years). p53-expression was not associated with DSS for any of the three cut-offs (cut-off1/2/3: P-log-rank = 0.566, 0.77 and 0.50, respectively). If we only considered locally advanced bladder cancer, results on DSS remained non-significant. Conclusion: This multi-center, multi-laboratory study showed that, regardless of the cut-off used, p53-immunohistochemistry did not enable selection of patients with worse outcome. Our results suggest that p53-immunohistochemistry alone is not suitable to guide clinical decision making after radical cystectomy.
Keywords: Prognosis; prognosis; retrospektivní studie; Humans; nádory močového měchýře; p53; geny p53; imunohistochemie; prognóza; Immunohistochemistry; Tumor Suppressor Protein p53; Genes, p53; nádorový supresorový protein p53; Urinary Bladder Neoplasms; bladder cancer; radical cystectomy; lidé; Cystectomy; cystektomie; Retrospective Studies; immunohistochemistry